The nexus between financial development and poverty reduction in Egypt - Vivian Bushra Kheir (Review of Economics and Political Science (REPS), 2018)
Purpose - The purpose of this study is to empirically examine the impact of financial development on poverty reduction in Egypt. The paper also investigates whether financial development affects poverty via gross domestic product (GDP) growth. Design/methodology/approach - This study uses the autoregressive distributed lag approach to estimate two specifications. The first is dependent on poverty by the ratio domestic credit to the private sector (percentage of GDP) and the second is dependent on the poverty by the ratio liquid liabilities to GDP or M3/GDP. The data are annual and cover the period from 1980 to 2015. Findings In long run, the study finds that relationship between economic growth and poverty is bidirectional. Financial development and poverty (household final consumption expenditure per capita) are complementary as bidirectional (in Granger sense). In short run, the study finds the bidirectional causality between financial development (real domestic credit to private sector per capita) and poverty reduction. Practical implications - The findings suggest that governments should remove policies that impede the ability of banks to offer loan products or undermine the commercial incentive structure for banks or borrowers. It is crucial to enhance the role of specialized state-owned banks in financial intermediation. Social implications - Several attempts have been made to investigate the relationship between financial development and other macroeconomic variables, but few studies have examined the impact of financial development on poverty reduction. Furthermore, the majority of the previous studies are based on Asia and Latin America - affording Egypt very little or no coverage at all.
Keywords: C22; D90; E40; G20; 330; Poverty; Egypt; ARDL; Financial development